Differences in health related quality of life valuations derived from country-specific SF-6D ‘tariffs’ (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
Measuring health outcomes is one of the key tasks in economic evaluation studies. One of the most common methodological options consists in deriving health-related quality of life measures from algorithms or ‘tariffs’ which assign values to health states, defined according to a descriptive system. In this paper we assess the differences between tariffs of one of these instruments, SF-6D, in Spain and other five countries, as well as the discrepancies that arise when tariffs are applied to a population sample. In both cases statistically significant differences emerge between countries and the widest rank of values results from the Spanish algorithm.
Keywords: Economic evaluation; health-related quality of life; health utilities; SF-6D; SF-36; tariffs.